Alcoholic liver disease: clinical and translational research - Neuman, Manuela G.; Seitz, Helmut K.; Mueller, Sebastian (Experimental and molecular pathology, 2015)
The present review spans a broad spectrum of topics dealing with alcoholic liver disease (ALD), including clinical research, translational research, pathogenesis and therapies. A special accent is placed on alcohol misuse, as alcohol is a legally commercialized and taxable product. Drinking alcohol, particularly from a young age, is a major health problem. Alcoholism is known to contribute to morbidity and mortality. A systematic literature search was performed in order to obtain updated data (2008-2015). The review is focused on genetic polymorphisms of alcohol metabolizing enzymes and the role of cytochrome p450 2E1 and iron in ALD. Alcohol-mediated hepatocarcinogenesis is also discussed in the presence or absence of co-morbidities such as viral hepatitis C as well as therapeutic the role of innate immunity in ALD-HCV. Moreover, emphasis was placed on alcohol and drug interactions, as well as liver transplantation for end-stage ALD. Finally, the time came to eradicate alcohol-induced liver and intestinal damage by using betaine.